2022
DOI: 10.3389/fnagi.2022.857902
|View full text |Cite
|
Sign up to set email alerts
|

Early Serum Metabolism Profile of Post-operative Delirium in Elderly Patients Following Cardiac Surgery With Cardiopulmonary Bypass

Abstract: BackgroundCardiac surgery with cardiopulmonary bypass (CPB) is considered to be one of the surgical types with the highest incidence of post-operative delirium (POD). POD has been associated with a prolonged intensive care and hospital stay, long-term neurocognitive deterioration, and increased mortality. However, the specific pathogenesis of POD is still unclear. Untargeted metabolomics techniques can be used to understand the changes of serum metabolites in early POD to discover the relationship between seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…The bands at 2912 and 1149 cm −1 are associated with lipids and carbohydrates, respectively, aligning with the known link between delirium and disruptions in the lipid metabolism and the energetic metabolism [39][40][41]43,59]. Indeed, these metabolic alterations serve as recognized indicators for post-operative delirium [39,43]. The bands at 942 and 1546 cm −1 , associated with proteins, and the band at 1041 cm −1 , linked to phosphate esters, along with those at 1268 and 987 cm −1 , related to phosphate groups (which can also be attributed to phosphorylated proteins and lipids), can be associated with the neuroinflammation, metabolic imbalances and oxidative stress in delirium [20,84].…”
Section: Multivariate Spectral Analysissupporting
confidence: 70%
See 2 more Smart Citations
“…The bands at 2912 and 1149 cm −1 are associated with lipids and carbohydrates, respectively, aligning with the known link between delirium and disruptions in the lipid metabolism and the energetic metabolism [39][40][41]43,59]. Indeed, these metabolic alterations serve as recognized indicators for post-operative delirium [39,43]. The bands at 942 and 1546 cm −1 , associated with proteins, and the band at 1041 cm −1 , linked to phosphate esters, along with those at 1268 and 987 cm −1 , related to phosphate groups (which can also be attributed to phosphorylated proteins and lipids), can be associated with the neuroinflammation, metabolic imbalances and oxidative stress in delirium [20,84].…”
Section: Multivariate Spectral Analysissupporting
confidence: 70%
“…Among these, bands at 2853, 2926 and 2961 cm −1 are associated with lipids, while the band at 1470 cm −1 is associated with both lipids and proteins. This association highlights the disruptive role of lipids in similar neurodegenerative diseases [43,[53][54][55][56][57][58]. For instance, Huang et al [43] observed significant changes in the lipid profiles of patients with post-operative delirium, hypothesizing that lipid dysregulation might contribute to the pathogenesis of the condition.…”
Section: Univariate Spectral Analysismentioning
confidence: 87%
See 1 more Smart Citation
“…These metabolic abnormalities most likely reduce the ability of the brain to provide neuroprotection and take part in neuroinflammatory responses. Another study applied untargeted metabolomics techniques to investigate the change of serum metabolites in POD patients undergoing cardiopulmonary bypass, and found that low serum lipid metabolic phosphatidylinositol was linked to an increased risk of POD in the geriatric patient, which may shed fresh light on the pathophysiology of POD ( Huang et al, 2022 ).…”
Section: Pathophysiological Changesmentioning
confidence: 99%
“…A compilation of 45 genes that were cited as POD markers and their role in the pathogenesis of POD extensively deliberated, were selected for analysis. Many of these genetic markers of POD are inflammatory factors, and their escalated levels have been documented in the plasma of POD patients in the preoperative and/or early postoperative period 55,56 . For instance, elevated plasma concentrations of interleukin 6 (IL6), tumor necrosis factor alpha (TNFA), and vascular endothelial growth factor (VEGF) have been detected in the early postoperative period in elderly patients who exhibited POD 57 .…”
Section: Reconstruction Of Gene Network Of Overrepresented Kegg Metab...mentioning
confidence: 99%